Hydrothermal synthesis of novel CoFe2O4/BiVO4 nanocomposites with enhanced visible-light-driven photocatalytic activities - Duangjam S. (2017)
© 2016 Elsevier B.V. The novel CoFe 2 O 4 /BiVO 4 nanocomposites were firstly synthesized by a facile hydrothermal method. The photocatalysts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET)-specific surface area, UV–vis diffuse reflectance spectrophotometer (UV–vis DRS), and X-ray photoelectron spectroscopy (XPS). The photocatalytic activities of all samples were evaluated based on the photocatalytic degradation of methylene blue (MB) under visible light irradiation. The results indicated that the photocatalytic activity of the CoFe 2 O 4 :BiVO 4 nanocomposite with the mole ratio of 0.2:0.8 was higher than that of pure CoFe 2 O 4 and pure BiVO 4 . The enhanced photocatalytic activity could be attributed to the formation of a composite, which suppressed the recombination of photogenerated electron-hole pairs. The formation of hydroxyl radicals (OH • ) was found as the oxidizing reactive species to cause the degradation of the MB. Based on the results, a reasonable mechanism of photocatalysis on CoFe 2 O 4 /BiVO 4 nanocomposite under visible light was proposed.